Unified cosmology with scalar–tensor theory of gravity - Behzad Tajahmad; Abhik Kumar Sanyal (European Physical Journal C: Particles and Fields, 2017)
Abstract Unlike the Noether symmetry, a metric independent general conserved current exists for non-minimally coupled scalar–tensor theory of gravity if the trace of the energy-momentum tensor vanishes. Thus, in the context of cosmology, a symmetry exists both in the early vacuum and radiation dominated era. For slow roll, symmetry is sacrificed, but at the end of early inflation, such a symmetry leads to a Friedmann-like radiation era. Late-time cosmic acceleration in the matter dominated era is realized in the absence of symmetry, in view of the same decayed and redshifted scalar field. Thus, unification of early inflation with late-time cosmic acceleration with a single scalar field may be realized.